Optimalisasi adaptasi neonatus dengan penerapan atraumatic care approach: swaddle dan sponge bath di Pangururan - Tambunan, Dior Manta; Silaen, Harsudianto; Simanullang, Rostime Hermayerni; Buaton, Kristina; Lumbantobing, Dikki Samuel (JOURNAL OF Public Health Concerns, 2024)
Background: Neonates experience a transition from the intrauterine to the extrauterine environment which can cause stress and have long-term consequences on the development of the baby's brain. One of the neglected and traumatic neonatal care is during the process of bathing the baby. Purpose: To improve the knowledge of posyandu cadres and the community about the application of the Atraumatic Care Approach: Swaddle and Sponge Bath in an effort to optimize adaptation in neonates. Method: Implementation of community service with pre-test and post-test, provision of cadres, health education and demonstration of the swaddle bath method at the Sait Nihuta Village Hall, Pangururan District. This activity was attended by 6 posyandu cadres, 25 community members consisting of mothers with children aged 0-5 months, pregnant women, and mothers who were planning to have their first/next child. By providing education in the form of material presentation, demonstration and simulation of the Atraumatic Care Approach: Swaddle and Sponge Bath care approach actions for participants. Results: Of the 6 posyandu cadres, there was an increase in knowledge about the Atraumatic Care Approach: Swaddle and Sponge Bath care approach of posyandu cadres from before (pre-test) PKM activities in the less category of 3 people (50.0%) to the majority in the good category of 4 people (66.7%) after (post-test) PKM activities. And for participants from the community, a total of 25 people also experienced an increase in knowledge about the Atraumatic Care Approach: Swaddle and Sponge Bath care approach from before (pre-test) PKM activities in the less category of 14 people (56.0%) to the good category of 15 people (60.0%) after (post-test) PKM activities. Conclusion: Educational activities through PKM can significantly increase knowledge of the Atraumatic Care Approach: Swaddle and Sponge Bath care approach in posyandu cadres and the community. The atraumatic care approach can minimize traumatic experiences during bathing in neonates. Suggestion: It is hoped that this program can continue through cadres who have received education through materials and demonstrations delivered to the community. Keywords: Atraumatic Care Approach; Neonates; Posyandu Cadres; Sponge Bath; Swaddle Bath Pendahuluan: Neonatus mengalami perpindahan dari lingkungan intrauterin ke ekstrauterin yang dapat menyebabkan stres dan mengakibatkan konsekuensi jangka panjang pada perkembangan otak bayi. Salah satu perawatan neonatus yang terabaikan dan traumatik adalah pada waktu proses memandikan bayi. Tujuan: Untuk meningkatkan pengetahuan kader posyandu dan masyarakat tentang penerapan pendekatan perawatan Atraumatic Care Approach: Swaddle  dan Sponge Bath dalam upaya mengoptimalkan adaptasi pada neonatus. Metode: Pelaksanaan pengabdian kepada masyarakat dengan pre-test dan post-test, pembekalan kader, edukasi kesehatan dan demonstrasi metode swaddle bath di balai Desa Sait Nihuta Kecamatan Pangururan. Kegiatan ini diikuti 6 orang kader posyandu, 25 orang masyarakat yang terdiri dari ibu yang mempunyai anak 0-5 bulan, ibu hamil, dan ibu yang merencanakan untuk mempunyai anak pertama/selanjutnya. Dengan memberikan edukasi berupa pemaparan materi, demonstrasi dan simulasi tindakan pendekatan perawatan penerapan Atraumatic Care Approach: Swaddle dan Sponge Bath pada peserta. Hasil: Dari sejumlah 6 orang kader posyandu terdapat peningkatan pengetahuan tentang pendekatan perawatan Atraumatic Care Approach: Swaddle  dan Sponge Bath kader posyandu dari sebelum (pre-test) kegiatan PKM dalam kategori kurang sebanyak 3 orang (50.0%) menjadi sebagian besar dalam kategori baik sebanyak 4 orang (66.7%) setelah (post-test) kegiatan PKM. Dan untuk peserta dari masyarakat sejumlah 25 orang juga mendapatkan peningkatan pengetahuan tentang pendekatan perawatan Atraumatic Care Approach: Swaddle dan Sponge Bath dari sebelum (pre-test) kegiatan PKM dalam kategori kurang sebanyak 14 orang (56.0%) menjadi dalam kategori baik sebanyak 15 orang (60.0%) setelah (post-test) kegiatan PKM. Simpulan: Kegiatan edukasi melalui PKM dapat meningkatkan pengetahuan pendekatan perawatan Atraumatic Care Approach: Swaddle  dan Sponge Bath yang signifikan pada kader posyandu dan masyarakat. Pendekatan perawatan atraumatik (Atraumatic Care Approach) dapat meminimalkan pengalaman traumatik selama dimandikan pada neonatus. Saran: Diharapkan program ini dapat berlanjut melalui kader yang telah menerima edukasi melalui materi dan demonstrasi yang disampaikan kepada masyarakat.